2004
DOI: 10.1136/vr.155.4.120
|View full text |Cite
|
Sign up to set email alerts
|

Apparent subclinical hepatopathy due to excess copper intake in lactating Holstein cattle

Abstract: a, b Means in the same column with different superscripts are significantly different (P<0.05) LF Low-forage diet, HF High-forage diet (OP111 1R toXiCit ill ildUlt dails'' Calttle iS bC1ing mici as''igls d1ta(ilos'ed in the L'K. 'I'lh \Vetetrmilars Laboratorie's icncv ccotrded 34 iniidenixts rom I980) to 1998, 1atid 33' separa.te 11be s \v c -alt-1tected ft o1il 1 999 to 20)0)2 (I is eCse C ld othitl-1)02. ).li It pritciple, coppet iiitoxicatioIn in cattlet is like the ctoIditiOti ill shlccp altiout (hli close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Several authors have postulated that hepatic enzymes may also be useful early markers during the long-term, subclinical phase of hepatic Cu accumulation, 21,23 on the basis of the fact that, during this silent phase, some cells undergo necrosis, leading to increases in enzyme activities in the blood. However, in line with the present results, other authors 35,41 have found only weak correlation between serum enzyme activities and hepatic Cu values or clinical manifestations of hepatic insufficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have postulated that hepatic enzymes may also be useful early markers during the long-term, subclinical phase of hepatic Cu accumulation, 21,23 on the basis of the fact that, during this silent phase, some cells undergo necrosis, leading to increases in enzyme activities in the blood. However, in line with the present results, other authors 35,41 have found only weak correlation between serum enzyme activities and hepatic Cu values or clinical manifestations of hepatic insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, however, an increasing number of episodes of Cu toxicosis have been reported in cattle, 6,23,40 even at Cu concentrations well below those regarded as toxic in the literature. 17,29 In most instances, Cu toxicosis in cattle is associated with excess Cu intake in the ration, as well as with changes in the type and bioavailability of dietary Cu supplements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, trace metals that are included as mineral supplements may have toxic effects at supra-optimal concentrations (Underwood and Suttle, 2002). For example, chronic Cu toxicity in cattle has been associated with excessive Cu intake in the concentrate ration, as well as with changes in the type and bioavailability of dietary Cu supplements (Galey et al, 1991;Laven et al, 2004). In addition, supplementing diets at concentrations in excess of requirement greatly increases mineral loss in cattle waste, and so should be avoided to prevent possible environmental problems associated with run-off from waste or application of cattle waste to soil (Vasconcelos et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…However, in recent years an increase in the number of episodes of Cu toxicity has been reported in cattle reared under intensive systems (Bidewell et al, 2000;VLA, 2001). Cu oversupplementation has been associated with subclinical hepatopathy and increase in liver enzymes without clinical signs of toxicity (Laven et al, 2004). It is widely accepted that diagnosis of chronic Cu toxicity is complicated and that health risk assessment cannot be based solely on Cu chemical analyses (Walker, 1998;Kakkar and Jaffery, 2005).…”
mentioning
confidence: 99%